Importance of Cytopathologic Diagnosis in Early Cancer Diagnosis in Resource-Constrained Countries. (25th February 2022) - Yadav, Kavita; Cree, Ian; Field, Andrew; Vielh, Philippe; Mehrotra, Ravi
Abstract : PURPOSE: The rising cancer burden in low- and middle-income countries (LMICs) stresses already weak health care systems and poses unique challenges. In resource-constrained LMICs and in circumstances where most patients must pay out of pocket for diagnostic tests, these may not be available or affordable for many. Cytopathology provides a simple, inexpensive, standardized, and low-technology diagnostic procedure that is increasingly used as an effective tool to address the hurdles faced in cancer control programs in LMICs. This review explores the potential role of cytopathology in LMICs in reducing the cancer burden. METHODS: This review studied the existing literature across the globe regarding the utilization of cytopathology as a diagnostic or screening tool for various types of malignancies as well as its advantages and disadvantages, depending on the local situation. RESULTS: Apart from the usefulness of cytopathology, this review also sheds light on the barriers to using cytopathology in LMICs. Most recently, SARS-CoV-2 has produced several unique challenges for cytopathology. These are being met with innovative measures to combat the effects of the pandemic and ensure the safe delivery of essential cytopathology services. CONCLUSION: The usefulness of cytopathologic techniques has been demonstrated via various studies, even during the recent pandemic. If cytology is to be used appropriately, the focus needs to be on integrating it into the national cancer screening and diagnostic programs as well as providing well-trained human resources.